ASSA13-11-16 Clinical Investigation of Effects of Intravenous Versus Intra-Coronary Injection of Tirofiban During Primary PCI. (29th April 2013) - Ying-Yan, Ma; Ya-Ling, Han; Quan-Min, Jing; Kai, Xu; Hai-Wei, Liu; Geng, Wang; Xiao-Zeng, Wang; Xin, Zhao
Abstract : Background: To investigate effects of intravenous versus intra-coronary injection of tirofiban on myocardial reperfusion during primary PCI in patients with STEMI. Methods: A total of 314 patients admitted to our hospital with myocardial infarction within 12 hours were enrolled in this study. Three hundred milligrammes aspirin and 600 mg clopidogrel were given before PCI. Patients were randomised into intra-coronary injection or intravenous injection of tirofiban (10 μg/kg). Primary endpoints included disappear of ST segments elevation, myocardial reperfusion grade, infarction size by cardiac biomarker and major adverse cardiac events within 30 days. Second endpoints include clinical events of bleeding. Results: There was no difference in rate of resolution of ST segments elevation (57% VS 58%). TIMI flow was better in intra-coronary group (84% VS 67%) and there was more myocardial reperfusion grade 2 (81% VS 63%). There was no difference in cardiac bio-marker level. There was no difference in rate of thrombocytopenia or major organ bleeding. Conclusions: Intra-coronary injection of tirofiban during primary PCI in patients with STEMI can result in better myocardial reperfusion grade, smaller infarction size, and better reperfusion, but has no effects on short-term prognosis. There was no increase of major clinical bleeding, so it is safe.